Studi Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan PT. Citra Nusa Insan Cemerlang (CNI) untuk Kategori Produk Food - Nita Felicia (Universitas Tarumanagara, 2020)
The rapid development of communication technologies in the future would give the negative impact to the concept of multi level marketing (MLM). Customers can easily purchase products in the online store by using their gadgets. In order to maintain company performance and optimum competitive advantage, the company should be able to understand customers’ behavior. This research aims to find out the effect of product quality, service quality and price on customer satisfaction, study case in the company of PT Citra Nusa Insan Cemerlang (CNI) as MLM company, particularly in food product category. The study was conducted by distributing questionnaire with 5 point of likert scale towards 171 respondents. The criteria for the respondents were must be member of CNI, know the variation of the food product of CNI and do purchase the food product of CNI within latest 3 months. The data were analyzed by using the Statistical Package for Social Sciences (SPSS) statistical software, version 24.0. The conclusion of this research is that product quality, service quality and price, for both partially and simultaneously, have a significant and positive effect on customer satisfaction. The effect of product quality, service quality and price on customer satisfaction respectively are 0,543, 0,359 and 0,411.